2016
DOI: 10.17795/jjcdc-43345
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge About Fecal Intestinal Ostomies’s Care: A Cross-Sectional Study

Abstract: Background: Investigation of various aspects of care in ostomy patients is of clinical importance, as the level of knowledge and skills of nurses directly influences the quality of patient education and satisfaction with received care. Objectives: The purpose of this study was to determine knowledge of nurses in general surgery wards regarding fecal intestinal ostomies. Methods: This cross-sectional study was performed during year 2015 at teaching hospitals (Ghaem, Imam Reza and Omid hospitals) affiliated to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…A pre-tested semi-structured, self-administered questionnaire was adapted from different previous works of literature and guidelines. 1,6,7,20,23 The questionnaire consists of socio-demographic characteristics, work and professional related data, nurses' knowledge towards colostomy care (8 true false and 17 multiple choice items with a total range of 0-25) and nurses' attitude towards colostomy care (9 questions with 5 point Likert scale: from "strongly agree = 5" to "strongly disagree = 1" with a total score range of 9-45). For this purpose, nine BSc nurses participated as data collectors.…”
Section: Quantitative Partmentioning
confidence: 99%
See 2 more Smart Citations
“…A pre-tested semi-structured, self-administered questionnaire was adapted from different previous works of literature and guidelines. 1,6,7,20,23 The questionnaire consists of socio-demographic characteristics, work and professional related data, nurses' knowledge towards colostomy care (8 true false and 17 multiple choice items with a total range of 0-25) and nurses' attitude towards colostomy care (9 questions with 5 point Likert scale: from "strongly agree = 5" to "strongly disagree = 1" with a total score range of 9-45). For this purpose, nine BSc nurses participated as data collectors.…”
Section: Quantitative Partmentioning
confidence: 99%
“…24 The guide was developed after literature review. 1,6,7,20,23 It was first developed in English and then translated to the local language (Amharic) to facilitate communication with participants. The interview questions focused on nurses' perceived responsibility and barriers encountered to perform colostomy care.…”
Section: Qualitative Partmentioning
confidence: 99%
See 1 more Smart Citation
“…( 7 ) Quality of care and training provided to patients can be associated with their subsequent QoL. A study done in one of the biggest hospitals in the country has shown that only half of the nurses among those who are responsible to prove ostomy care have good knowledge and skill to give care and training to patients ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…No exterior e no Brasil, outras pesquisas realizadas mensuraram qualidade de vida (8) e cuidados da estomia (9)(10) . Recentemente, Estados Unidos e Irã validaram instrumentos para avaliar conhecimento de enfermeiros sobre estomias intestinais de eliminação (4,11) . Mas, nenhum destes instrumentos possibilitava avaliação do conhecimento de graduandos de Enfermagem e enfermeiros sobre o cuidado no perioperatório de cirurgias geradoras de estomias intestinais de eliminação.…”
Section: Introductionunclassified